2018
DOI: 10.3758/s13420-018-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated dogs (Canis familiaris) tend to follow repeated deceptive human cues even when food is visible

Abstract: There is abundant evidence that domestic dogs (Canis familiaris) readily follow pointing and other cues given by humans. But there has been much less research into the question of whether dogs can learn to discriminate between different humans giving repeated honest or dishonest cues as to food location, by ignoring the information imparted by the deceiver. Prior research has demonstrated that even after repeated exposures to deceptive cues with respect to food location, dogs failed to learn to ignore those cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that dogs are more likely to choose an empty bowl out of two choices if a human points towards it, even when they have seen that the other bowl has food in it [34][35][36][37] . Similar to the gesture tests, this test aims to measure social cognition.…”
Section: Memory Vs Gesturementioning
confidence: 99%
“…Previous studies have shown that dogs are more likely to choose an empty bowl out of two choices if a human points towards it, even when they have seen that the other bowl has food in it [34][35][36][37] . Similar to the gesture tests, this test aims to measure social cognition.…”
Section: Memory Vs Gesturementioning
confidence: 99%
“…Shortly later, Miklósi, Polgárdi, Topál, and Csányi [15] used the object-choice task on the first set of dog subjects; they found that dogs were able to reliably follow a point to find the rewarded container. Domestic dogs have also been found to follow human cues even when the cue is counterproductive, as some dogs chose empty cups, over cups with rewards [16]. Dogs have very powerful olfactory senses, and they will use this sense to find rewards in object-choice tasks [17]; however, when human cues are provided, dogs have been reported to privilege these cues over their own senses [18,19].…”
Section: Introductionmentioning
confidence: 99%